PulsePoint dispatch associated patient characteristics and prehospital outcomes in a mid-sized metropolitan area. (January 2022) - Smida, Tanner; Salerno, Jessica; Weiss, Leonard; Martin-Gill, Christian; Salcido, David D.
Abstract: Background: Mobile phone-based dispatch of volunteers to out-of-hospital cardiac arrests (OHCA) has been shown to increase the likelihood of early CPR and AED application. In the United States, limited characterization of patients encountered as a result of such systems exists. Aims: Examine prehospital case characteristics and outcomes from a multi-year deployment of PulsePoint Respond in Pittsburgh, Pennsylvania. Methods: PulsePoint event timing, location, and associated prehospital electronic health records (ePCRs) were obtained for EMS-encountered OHCA cases that did and did not generate PulsePoint alerts within the service area of Pittsburgh EMS from July 2016 to October 2020. ePCRs were reviewed and OHCA case characteristics were extracted according to the Utstein template. PulsePoint-associated OHCA and non-PulsePoint-associated OHCA were compared. Results: Of 840 total PulsePoint dispatches, 64 (7.6%) were for OHCA associated with a resuscitation attempt. Forty-one (64.1%) were witnessed, 38 (59.4%) received bystander CPR, and 13 (20.0%) of these patients had an AED applied prior to EMS arrival. Twenty-seven (39.7%) had an initial shockable rhythm, and 31 (48.4%) patients achieved ROSC in the field. In the city of Pittsburgh, there were 1229 total OHCA during the study period, with an estimated 29.6% occurring in public. When PulsePoint-associated and publicly occurring non-PulsePoint-associated OHCA were compared, baseline characteristics (age, sex, witnessed status) were similar, but PulsePoint-associated OHCA received more bystander CPR (p = 0.008). Conclusions: A minority of PulsePoint dispatches in Pittsburgh were triggered by true OHCA. The majority of OHCA during the study period occurred within private residences where PulsePoint responders are not currently dispatched. PulsePoint dispatches were associated with prognostically favorable OHCA characteristics and increased bystander CPR performance.